PENERAPAN VIDEO SENAM KESEGARAN JASMANI 2012 UNTUK MENINGKATKAN GERAKAN SENAM KESEGARAN JASMANI SISWA KELAS V SD NEGERI 1 PANGGUNG BARAT MAGETAN - Titin Kuntum Mandalawati (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2013)
This research purposes to improve the movements of the fifth graders of the elementary school SD Negeri 1 Panggung Barat Magetan by applying the Gymnastic Video of “SenamKesegaranJasmani (SKJ)” 2012. This is a Classroom Action Research (CAR). The source of data are the fifth graders of SDN I Panggung Barat Magetan as many as 30. Data were collected through tests and observation. They are qualitatively described and the percentage of the distribution is provided. Results show that applying the SKJ video improved the movements of the fifth graders of SDN I Panggung Barat Magetan as indicated by the tests on their movements before and after the application of the video. The descriptive qualitative analysis improvements were visible on the cycle I, II and III in which there were three action meetings. In the first cycle it focused on the warming up, core and cooling-down movements. In the final meeting of the first cycle, a test was administered. In the first cycle it found improvement of 30% out of the 30 students i.e. 9 students. In the second cycle was reflection on the first cycle and another movement was added. In this cycle the emphasis was on the core movements and repeating the warming up and introducing the cooling-down ones. In thi final meeting of this cycle, a test was administered and all students took part. The second cycle witnessed improvement of 60%, 19 out of 30 students. The third cycle was a reflection on the second cycle in addition to another movement introduction. This cycle emphasized on the cooling-down movements and repetition on the warming up and core movements. In the final meeting, a test was administered to know whether or not the students improved. All of them participated. In this cycle it was found improvement of 75%, or 23 out of 30 students. However, there were 25 of them who could perform correctly. The percentage, therefore, changes into 80%. This is higher than the expected one on the third cycle. It is also revealed that 19.4% or 6 students were not able to perform the gymnastic correctly. Key words: SKJ 2012 Video, Gymnastic Movements